Injury prevention programs for throwing injuries in softball players: A systematic review - Paul, J.; Brown, S. M.; Mulcahey, M. K. (Sports Health: A Multidisciplinary Approach, 2021)
Context: Throwing-related injuries occur commonly in softball players. Preventative programs can be implemented to assist in identifying and correcting risk factors that could potentially lead to injury and therefore time missed from both practice and games. Objective: The purpose of this study was to determine if position-specific injury prevention programs have been developed to decrease the risk of throwing-related injuries in softball players. Data Sources: A systematic review was performed using the PRISMA (Preferred Reporting Items of Systematic Reviews and Meta-Analyses) guidelines. PubMed, PMC, and EBSCO were searched for articles on injury prevention programs using the following key terms: softball, injury prevention, throwing injuries, pitcher, and shoulder. Study Selection: Studies that involved fast-pitch softball and included female participants as well as rehabilitation programs were included. Articles that highlighted slow-pitch softball or did not include female participants were excluded. Level of Evidence: Level 1. Data Extraction: The initial search identified 1605 articles. After implementing a filter, 131 articles remained. Thirteen articles were screened out as duplicates. After screening for inclusion criteria, 7 articles remained and were included in the systematic review. Results: Decreased range of motion (ROM) in both the upper and the lower extremities, unbalanced muscular strength, and fatigue were identified as risk factors for throwing injuries in softball players. Within the upper extremity, strength and ROM of the rotator cuff muscles, biceps, and extensors of the forearm were emphasized. The main focus of the lower extremity was the strength of the gluteal muscles and ROM of the lumbopelvic-hip complex. Only 1 study detailed an injury prevention program for softball players. The prevention program outlined was generalized for all softball players and was not position specific. Conclusion: There is a paucity of information about injury prevention programs for softball players. Of the evidence analyzed, balanced strengthening of the upper and lower extremities while maintaining dynamic range of motion was frequently utilized in developing an injury prevention program.